PERLAKUAN AKUNTANSI AKTIVA TETAP BERWUJUD DAN PENYAJIANNYA DALAM LAPORAN KEUANGAN PADA CV. BAHANA KARYA GRESIK - AGUS ISMAWATI, CATUR (Jurnal Pendidikan Akuntansi (JPAK), 2013)
Accounting is one of the means to manage the tangible fixed assets to suit the needs of the company. Accounting has the basics of accounting process begins when the tangible fixed assets acquired tangible fixed assets to tangible fixed assets are released or waived. Issues to be discussed further in this study is "How Accounting Treatment of Intangible and tangible fixed assets in the Financial Statements Presentation on the CV. Bahana Karya Gresik ". Type of research in this thesis is a qualitative descriptive that provides an overview of the application of accounting for fixed assets owned by the company and the presentation in the financial statements. In conducting this study the authors use the method of data collection by observation, interviews, and documentation. Based on the results of this study are CV. Bahana Karya Gresik in performing the recognition, measurement, depreciation, decommissioning, and disclosure of the fixed assets is not in accordance with PSAK No.. 16. Key word : fixed Assets, Financial Statements